Efektivitas Penggunaan SIA, Kemampuan Teknis Pengguna, Ekspektasi Usaha, dan Kinerja Individual LPD - Surya Kinanti, Putu Indy; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2023)
The Village Credit Institution (LPD) is a financial institution owned by Pakraman village to manage the finances of the local village community. The increase and development of LPD is driven by information technology which is increasingly developing rapidly. The research was conducted to obtain empirical data about the influence of the effectiveness of AIS use, users' technical abilities and effort expectations on individual performance. Denpasar City LPD was used as the research location with a population of 237 people. The sample was determined using the nonprobability sampling method and purposive sampling technique. The data analysis technique in this research is multiple linear regression. The research output reveals that the effectiveness of using AIS, users' technical abilities, and business expectations have a positive and significant influence on the individual performance of Village Credit Institutions in Denpasar City. The results of this research support the Technology Acceptance Model (TAM) to make things easier for users. Keywords: Effective Use of AIS; User Technical Capabilities; Business Expectations; Individual Performance